Morphological anomalies in hard ticks (Acari: Ixodidae) from Brazil - Luz, Hermes R.; Labruna, Marcelo B.; Pacheco, Richard C.; Gianizella, Sergio L.; Nunes, Pablo H.; Szabó, Matias P.J.; Gerardi, Monize; Teixeira, Rodrigo H.F. [UNESP]; da Silva, Silvio C.; Kmetiuk, Louise B.; Pesenato, Isabella P.; Marcili, Arlei; et al. (Elsevier, 2023)
Tick abnormalities have been unusual in nature, and they can be divided into local and general. In the present study, external morphological anomalies were described in 31 individual adult ticks of 15 different species of Ixodidae, which were collected on wild hosts (20 ticks), domestic hosts (7 ticks), and in the environment (4 ticks) in 11 states of Brazil from 1998 to 2022. Among the 31 tick specimens, 14 (45%) were categorized as local anomalies, and 17 (55%) as general anomalies. The ticks were taxonomically identified into 14 species of Amblyomma, and one species of Rhipicephalus. Local anomalies included malformations of scutum/alloscutum, ectromely, leg atrophy, and a third ectopic spiracular plate. General anomalies included opisthosoma duplication, no expansion of dorsal alloscutum in engorged females, and gynandromorphism; the latter is described for 13 tick specimens. Morphological anomalies in Amblyomma aureolatum, Amblyomma brasiliense, Amblyomma humerale and Amblyomma longirostre are reported for the first time. Although the results herein expand the list of anomalous tick species in the Neotropics, future studies should be conducted to clarify the origin of these anomalies.
Keywords: Amblyomma; Gynandromorphism; Neotropical region; Rhipicephalus